Anaesthetic Considerations in a Patient with Pycnodysostosis undergoing Caesarean Delivery - Niklas S. Hansen; Karoline S. Dalgaard; Troels B. Jensen (Case Reports in Anesthesiology)
Pycnodysostosis is a rare congenital disorder with several implications, which might complicate anesthesia. Patients are more prone to fractures and have an anticipated difficult airway. We report a case of a 34-year-old woman with pycnodysostosis who underwent elective caesarean delivery under epidural blockade.